2022
DOI: 10.1093/ntr/ntac085
|View full text |Cite
|
Sign up to set email alerts
|

Active Smokers Are at Higher Risk of COVID-19 Death: A Systematic Review and Meta-analysis

Abstract: Introduction Current evidence indicates that smoking worsens COVID-19 outcomes. However, when studies restricted their analyses to current smokers, the risks for COVID-19 severity and death are inconsistent. This meta-analysis explored the association between current smoking and the risk for mortality based on the studies that reported all three categories of smoking (current, former, and never smokers) to overcome the limitation of the previous meta-analyses which former smokers might have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 62 publications
2
27
2
Order By: Relevance
“…Emerging evidence seems to support an association between smoking and more severe COVID-19 outcomes. [55,56] However, more women than men smoke daily in Sweden, although the difference is marginal. [57] Therefore, it is not likely that smoking status is a major driver of the observed sex disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence seems to support an association between smoking and more severe COVID-19 outcomes. [55,56] However, more women than men smoke daily in Sweden, although the difference is marginal. [57] Therefore, it is not likely that smoking status is a major driver of the observed sex disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent meta-analysis of observational studies showed that current and former smokers had higher risk of COVID-19 death. 3 …”
Section: Interpreting the Wider Evidence Basementioning
confidence: 99%
“… 4 (not included by Simons et al . 3 ) combining observational analysis and Mendelian randomization using the UK Biobank cohort, which reported that current smoking was associated with elevated risk of severe COVID-19. Gao et al .…”
Section: Interpreting the Wider Evidence Basementioning
confidence: 99%
“…According to currently available data, the role of smoking, tobacco, or other nicotine inhalation delivery systems’ use in acquiring SARS-CoV-2 infections is not established. In contrast, the harmful effect of tobacco smoking on the severity and mortality of COVID-19 is well-established [ 5 , 12 , 15 , 16 , 17 , 18 , 19 ]. This means that current regulatory strategies [ 20 ] to fight the tobacco epidemic should not be changed.…”
Section: Regulatory Considerationsmentioning
confidence: 99%